Cognitive behavioural therapy for older adults with depression: a review. (June 2015) - Jayasekara, Rasika; Procter, Nicholas; Harrison, Julie; Skelton, Kerim; Hampel, Sally; Draper, Russell; Deuter, Kate
Abstract Background: Depression is a major public health concern of global significance. The illness diminishes overall quality of life and has been associated with significant distress and disability in physical, interpersonal, and social role functioning. Over the past few decades, a consensus has evolved that cognitive behavioural therapy (CBT) can be an effective treatment for depression in older adults; however, little attention has been given to its effect on them. Aims: The purpose of this review was to examine the current use of CBT and its effect on older adults with depression. Method: A web-based literature search was performed to identify original research articles published from 2000 to 2013 using a three-step search strategy. Results: Evidence indicates that cognitive behavioural therapies are likely to be efficacious in older people when compared with treatment as usual. This is consistent with the findings of several systematic reviews and meta-analyses undertaken across a wider age range. Conclusions: Given that many older adults with depression are reluctant to accept antidepressant medication or unable to tolerate their side effects, CBT can be used as an option in treating depression in older adults.